HADIS ORANG BODOH MASUK SURGA - Siti Chuzaemah (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper discusses the quality of the hadith of Inna Akṡar Ahl al-Jannah al-Bulhu contained in Musykil al-Ᾱtṡār by Imām al-Ṭaḥāwī. Although the quality of the hadith is ḍa‘īf, in terms of observance of the tradition it is ṣaḥīḥ. This paper also dialogues the contradiction between the hadith and the Qur’an, and the resolution of the problem by using the Jam‘ Yūsuf al-Qarḍāwī method and Maḥmūd al-Ṭaḥḥān.